Cox proportional hazards models with left truncation and time‐varying coefficient: Application of age at event as outcome in cohort studies. Issue 3 (3rd February 2017) - Kim, Minjin; Paik, Myunghee Cho; Jang, Jiyeong; Cheung, Ying K.; Willey, Joshua; Elkind, Mitchell S. V.; Sacco, Ralph L.
Abstract : When analyzing time‐to‐event cohort data, two different ways of choosing a time scale have been discussed in the literature: time‐on‐study or age at onset of disease. One advantage of choosing the latter is interpretability of the hazard ratio as a function of age. To handle the analysis of age at onset in a principled manner, we present an analysis of the Cox Proportional Hazards model with time‐varying coefficient for left‐truncated and right‐censored data. In the analysis of Northern Manhattan Study (NOMAS) with age at onset of stroke as outcome, we demonstrate that well‐established risk factors may be important only around a certain age span and less established risk factors can have a strong effect in a certain age span.